The effectiveness of ‘secure and guard’ (SG) method and 14 protocol against illegal dumping of solid waste in Wilayah Persekutuan Kuala Lumpur (WPKL) - Jaharudin, Siti Noraen (2019)
Illegal dumping of waste is a man-made-disaster which now increasing and leads to environmental harms. Several countries have been experimenting with their own programs in an effort of against illegally dumping waste. In Malaysia, Solid Waste Corporation (SWCorp), the organization that responsible in implementing and enforcing solid waste management, law and public cleaning has introduced Secure and Guard (SG) method and 14 Protocol (14P) in early 2013 in order to handle the issues of illegal dumping waste. Thus, this case study focused on investigating the effectiveness of Secure and Guard (SG) method and 14 Protocol (14P). Location of study is in 3 zones of Wilayah Persekutuan Kuala Lumpur (WPKL) which consists of North WPKL, Centre WPKL and South WPKL. The secondary data were collected from SWCorp and analysed using Pair T-Test. A survey by questionnaires was carried out to validate results of case studies which respondents are among SWCorp officers that have more than 5 years experience dealing with illegal dumping. Seven (7) other methods were identified from the literature review i.e.: Web-based Application (SI-WEB-GIS); (2) Remote Sensing; (3) CCTV; (4) GIS-Based Zoning; (5) GIS Techniques; (6) Waste Management Act; and (7) Ground-Penetrating Radar (GPR) . The best method to increase the effectiveness of curbing illegal dumping waste issues. The contribution factor of illegal waste dumping were determined and using Average Index. The significant findings of this study showed that the SG method and 14P is not fully effective. The best method that may increase the effectiveness in handling illegally dumping waste is strengthening the waste management act and amendments of the act from time to time. The main factor of illegally waste dumping is transportation to long distance landfills. Enforcement of appropriate acts will ease the process of handling the case of illegal dumping in the country.